Governmental Fictions: The Naturalist Novel and the Making of Population in Fin-de-Siècle Brazil - Halaburda, Carlos Gustavo (Taller de letras, 2020)
In this article, I want to explore three Brazilian fin-de-siecle novels that inaugurated a true aesthetic revolution that would have as its main subject of interest the governmentality of bourgeois conduct. A carne (1888) by Julio Ribeiro, A intrusa (1908) by Júlia Lopes de Almeida, and Hóspede (1887) by Pardal Mallet allow an examination of how the novel in turn-of-the-century Brazil assumed a governmental strategy of sex. I argue that these nation-building writers/pedagogues promoted a program of sexual conduct oriented toward the conservation of the institutionality of marriage, family, and reproduction. I demonstrate how female education not associated with the domestic space, inter-class marriage, promiscuity, and adultery were portrayed as transgressions against the biological futures of patrician circles.